Perception of Media Literacy in the Education Community - Arsenijević, Jasmina M.; Andevski, Milica J. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The aim of the study is to analyze the perception of media literacy of educational community (high school and college students, higher educational population and masters of science) using a combination of qualitative and quantitative research methods. The survey was conducted during 2021. Technique of interview was used on a sample of 120 participants about participants’ perceptions of media literacy. Total 107 participants gave complete responses, and the results are evaluated based on established categories according to the level of accuracy of answers. Categories are formed according to content analysis and cross-referenced with socio-demographic characteristics. Having in mind a favourable educational structure of the research sample, the starting thesis is that respondents will have a clear understanding of media literacy. The results indicate that the majority of participants properly perceive media literacy in terms of critical reflection of media content, but not as the ability to produce media content as an essential characteristic of participatory culture, which leaves space for improvement and development of a productive cooperation of media users, as the inevitable trend of modern, media-driven society. The qualitative nature of this study enabled the recognition of diverse and deeper categories of phenomena of media literacy in current scientific knowledge. This qualitative approach of the comprehension of media literacy provided insights that are valuable as theoretical contribution, but are first and foremost a precious asset for the creators of media policy, especially for media education strategies.
Keywords: media literacy; media education policy; qualitative research